2009
DOI: 10.1186/1471-2334-9-42
|View full text |Cite
|
Sign up to set email alerts
|

HIV care and treatment factors associated with improved survival during TB treatment in Thailand: an observational study

Abstract: BackgroundIn Southeast Asia, HIV-infected patients frequently die during TB treatment. Many physicians are reluctant to treat HIV-infected TB patients with anti-retroviral therapy (ART) and have questions about the added value of opportunistic infection prophylaxis to ART, the optimum ART regimen, and the benefit of initiating ART early during TB treatment.MethodsWe conducted a multi-center observational study of HIV-infected patients newly diagnosed with TB in Thailand. Clinical data was collected from the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 19 publications
(17 reference statements)
5
45
1
Order By: Relevance
“…In other studies, the overall mortality was related to extrapulmonary TB, tuberculous meningitis, disseminated TB infection, MDR-TB, low CD4þ count and delay or failure to start cART. 7,18,19,35,36 Our study demonstrated that the only independent risk factor for death was disseminated infection. This finding might be explained by the fact that patients with disseminated infection would have a higher bacterial load of M. tuberculosis and thus more severe immunodeficiency status.…”
Section: Discussionmentioning
confidence: 81%
“…In other studies, the overall mortality was related to extrapulmonary TB, tuberculous meningitis, disseminated TB infection, MDR-TB, low CD4þ count and delay or failure to start cART. 7,18,19,35,36 Our study demonstrated that the only independent risk factor for death was disseminated infection. This finding might be explained by the fact that patients with disseminated infection would have a higher bacterial load of M. tuberculosis and thus more severe immunodeficiency status.…”
Section: Discussionmentioning
confidence: 81%
“…Three studies explicitly reported on how death was ascertained or confirmed (Table 2) [38], [39], [45].…”
Section: Resultsmentioning
confidence: 99%
“…This view is supported by an observational study that showed no difference in mortality between HIV-infected patients with smear-positive and smear-negative pulmonary tuberculosis or extrapulmonary tuberculosis. 24 …”
Section: Discussionmentioning
confidence: 99%